2010
DOI: 10.1021/es100679f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Toxicity Assessment of Nanomaterials by Whole-Cell-Array Stress Genes Expression Analysis

Abstract: This study performed mechanistic toxicity assessment of nanosilver (nAg) and nanotitanium dioxide anatase (nTiO2_a) via toxicogenomic approach, employing a whole-cell-array library consisting of 91 recombinated Escherichia coli K12 strains with transcriptional GFP-fusions covering most known stress response genes. The results, for the first time, revealed more detailed transcriptional information on the toxic mechanism of nAg and nTiO2_a, and led to a better understanding of the mode of action (MOA) of metal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 36 publications
7
127
0
Order By: Relevance
“…The protein expression levels based on GFP signals were calculated using the method previously described (39,40). The raw data from the OD 600 and GFP measurements were corrected by considering the background signals in control with medium only, and the protein expression per cell unit for each measurement was calculated by normalizing the GFP data to the cell number (OD 600 ), with P equal to the GFP measurement over the OD 600 .…”
Section: Methodsmentioning
confidence: 99%
“…The protein expression levels based on GFP signals were calculated using the method previously described (39,40). The raw data from the OD 600 and GFP measurements were corrected by considering the background signals in control with medium only, and the protein expression per cell unit for each measurement was calculated by normalizing the GFP data to the cell number (OD 600 ), with P equal to the GFP measurement over the OD 600 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, enzyme-linked immunosorbent assays, which use specific antibodies and enzymes, have been widely used for the low-level analysis of molecules. The specific association of AgNPs with cell surface proteins [12] and the differential expression of bacterial stress response genes with AgNPs and TiO 2 nanoparticles [13] indicate that biological reporter systems [14] that are highly specific to nanoparticle surfaces could be developed. Biosensors are very sensitive and, because they report on interactions of nanoparticles with living systems [15,16], should provide assessments of bioavailable fractions of nanoparticles, which are highly relevant to understanding exposure.…”
Section: Use Of Biological Sensors: Alternative Approachmentioning
confidence: 99%
“…Pure culture studies regularly report both acute toxicity and sublethal effects of ENPs on bacteria through mechanisms including membrane disorganization, DNA damage, surface-coating-related photocatalytic oxidation, and reactive oxygen species (ROS) production (5,10,23,44). This suggests that ENPs could be toxins when released into soil, e.g., harming or killing microorganisms.…”
Section: Do Enps Affect Soil Bacterial Communities?mentioning
confidence: 99%
“…Previous studies also demonstrated distinct effects of nano-TiO 2 on phyllosphere microbial communities (51), activated sludge bacterial communities (56), and microbial biofilms in stream microcosms (3), which partially support our observations in the terrestrial system studied here. The potential mechanism could be the direct toxicity of ENPs on soil bacteria through the release of metal ions or attachment-related cell damage (5,10,23,28,44). ENPs may also indirectly affect soil bacteria by changing nutrient availability or the bioavailability of cooccurring contaminants and by changing physical properties of the soil due to their large surface area and high reactivity (4,25).…”
Section: Do Enps Affect Soil Bacterial Communities?mentioning
confidence: 99%